2016
DOI: 10.19081/jpsl.2016.6.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change and Spatial Utilization in Landslide Vulnerable Regions of Banjarnegara Regency, Central Java

Abstract: The relatively constant availability of land in a region causes competition in its utilization with various landuse-change consequences. One of which is being the important triggering factors of landslide hazard, particularly in vulnerable regions, such as those working in Banjarnegara Regency, Central Java. This research was aimed at: (1) to identify landuse changepattern in 2001-2015 periods, and (2) to evaluate spatial utilization or existing land use consistencytowards spatial pattern allocated in RTRW of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The built-up land cover also experienced a significant increase in the area due to large changes (>40,000 ha) contributed by changes in non-field agricultural land cover and rice fields. The built-up land area increases due to space requirements, population growth, economic growth, and the fulfilment of facilities to support human activities [17] [18] [19]. The level of development of districts/cities in Central Java Province in 2014 and 2019 based on the regional development index is presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The built-up land cover also experienced a significant increase in the area due to large changes (>40,000 ha) contributed by changes in non-field agricultural land cover and rice fields. The built-up land area increases due to space requirements, population growth, economic growth, and the fulfilment of facilities to support human activities [17] [18] [19]. The level of development of districts/cities in Central Java Province in 2014 and 2019 based on the regional development index is presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…There are lands incompatible for cultivation including timber plantation, plantation, dryland agriculture, and mixed dryland agriculture. Ramadhan et al (2016) claimed that land situated on >40% of slope are vulnerable to erosion and landslide. Yi et al, (2010) who did research in Enshi, China declared that human activities in using land for dryland agricultural cultivation and farms play important role in accelerating soil weathering which resulted in slope instability.…”
Section: Lands Potential For Agricultural Development In Santan 2 Watmentioning
confidence: 99%
“…The changes of forest areas into agricultural lands also cause damages in the ecosystems at watershed level as considerable areas in the landscape become incompatible with its capability, affecting its carrying capacity and quality (Sinukaban 2007;Harjianto et al 2016). Ramadhan et al (2016) reported that incompatibility in terms of the use of an area could cause landslide problems. Large changes in land uses without taking into account natural resources sustainability and environmental functions would cause land degradation which may trigger erosion, sedimentation, flood, and landslide in watershed ecosystems.…”
Section: Introductionmentioning
confidence: 99%